Navigating educational challenges amidst civil unrest: An in-depth exploration of the impact on access in the north and south-west region of Cameroon - Hennades T Tabe; Raymond Emekako (Perspectives in Education)
Expanded educational opportunities symbolise the development of civil society and reflect the government’s commitment to the nation’s people. Unlike other parts of Africa, such as Sudan, which is known for its high level of civil unrest, Cameroon has traditionally experienced relative tranquillity. However, recent years have seen a surge in civil unrest, particularly in the North-West and South- West regions, profoundly affecting educational access. Through indepth interviews, this qualitative research investigates the intricate dynamics of how civil unrest significantly impacts educational access for students, teachers, parents and community leaders in conflict-affected regions. By employing a phenomenological inquiry design, the study aims to capture the lived experiences and understanding of 16 purposefully selected stakeholders across the community. Findings from the interviews highlight a disruption of normalcy in educational institutions, with schools frequently forced to close because of security concerns, impacting the quality of education. Challenges in Commuting to and from schools present challenges and fears of abduction. Also, the imposed ‘ghost town’ school disruptions on Mondays have led to irregular attendance. The socio-political context also influences curricular content, shaping the perspectives and values imparted to students. The study aimed to inform policy formulation and intervention strategies. The need for practical recommendations to mitigate the adverse effects of civil unrest and its effects on educational access in conflict-ridden regions of Cameroon was essential. By understanding how civil unrest affects education, this study contributes to the growing body of research on the impact of conflict, providing a nuanced perspective that considers the local context and amplifies the voices of those directly affected.